Isolated diffuse type B-cell lymphoma of the palate: an unusual entity. (23rd May 2013) - Roche, Phoebe; O'Neill, Paul; Kavanagh, Eoin; Rowley, Helena
Abstract : Lymphomas frequently occur as extranodal lesions in the head and neck, but are rarely seen in the palate. We present a case of isolated diffuse type B-cell lymphoma of the palate, which occurred in a 28-year-old man. The patient had no history of immune compromise, and he presented to the emergency department with a 7-month history of a painful, non-healing ulcerative mass in the hard and soft palate. Positron emission tomography facilitated pretreatment assessment of the extent and activity of the lesion. Histopathological and immunohistochemical analyses of biopsied tissue confirmed a diagnosis of diffuse type B-cell lymphoma. The clinical findings and therapeutic challenges in this heterogeneous group of malignancies are discussed.